An examination of the business case for transparency and accountability in the non-profit sector in Swaziland - Simelane, Vulindlela Sibonginkhosi (My University, 2015)
The primary objective of the research study was to investigate the salience of transparency and accountability in Swaziland’s Non-Governmental Organization (NGO) Sector. To this end, the study had a particular focus on the relationship between compliance with transparency and accountability and the increased ability to mobilize external funding. The key motivating factor behind this assessment was the rise to prominence of corporate governance best practice across the globe. To achieve this paramount objective, the existing body of knowledge on NGO transparency and accountability was consulted extensively. This was aimed at situating the research study in an empirically grounded context. In addition, the appropriate research methodology was adopted with a view to arriving at credible conclusions on the actual facts on the ground. While the strong focus of the study was NGO transparency and accountability, the findings revealed that there were underlying factors that created a cause-effect relationship between the quality of transparency and accountability, and the ability of NGOs to mobilize resources effectively. In this regard, it was found the institutional capacity was the defining factor, and or independent variable that determined the levels of transparency and accountability, and by extension, funding ranking. In conclusion, the research report, recommends that the NGO sector, particularly at the local level be professionalized in order to ensure that stronger institutions in the NGO sector are fostered.
Thesis (M.M. (Public and Development Management))--University of the Witwatersrand, Faculty of Commerce, Law and Management, School of Governance, 2014.